2015
DOI: 10.1101/gr.177576.114
|View full text |Cite
|
Sign up to set email alerts
|

SETDB1 modulates PRC2 activity at developmental genes independently of H3K9 trimethylation in mouse ES cells

Abstract: SETDB1, a histone methyltransferase responsible for methylation of histone H3 lysine 9 (H3K9), is involved in maintenance of embryonic stem (ES) cells and early embryonic development of the mouse. However, how SETDB1 regulates gene expression during development is largely unknown. Here, we characterized genome-wide SETDB1 binding and H3K9 trimethylation (H3K9me3) profiles in mouse ES cells and uncovered two distinct classes of SETDB1 binding sites, termed solo and ensemble peaks. The solo peaks were devoid of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 47 publications
5
26
0
Order By: Relevance
“…For comparison to other ChIP-seq data sets, we analyzed published datasets: ATRX (GSM551138)(Law et al, 2010), CTCF (GSM1540992)(Kung et al, 2015), Ezh2 (GSM905437)(Pinter et al, 2012), PolIIS5 (GSM905442)(Pinter et al, 2012), H3K4me3 (GSM905439)(Pinter et al, 2012), H3K9me3 (GSM1531184)(Fei et al, 2015), H3K27me3 (GSM905438)(Pinter et al, 2012), SMC1 (GSM560341)(Kagey et al, 2010) and H3K36me3 (GSM905441)(Pinter et al, 2012). Fastq files were aligned to the mm10 genome using Bowtie2 (-k 1 –very-sensitive –no-disordant) (Langmead and Salzberg, 2012).…”
Section: Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison to other ChIP-seq data sets, we analyzed published datasets: ATRX (GSM551138)(Law et al, 2010), CTCF (GSM1540992)(Kung et al, 2015), Ezh2 (GSM905437)(Pinter et al, 2012), PolIIS5 (GSM905442)(Pinter et al, 2012), H3K4me3 (GSM905439)(Pinter et al, 2012), H3K9me3 (GSM1531184)(Fei et al, 2015), H3K27me3 (GSM905438)(Pinter et al, 2012), SMC1 (GSM560341)(Kagey et al, 2010) and H3K36me3 (GSM905441)(Pinter et al, 2012). Fastq files were aligned to the mm10 genome using Bowtie2 (-k 1 –very-sensitive –no-disordant) (Langmead and Salzberg, 2012).…”
Section: Methods Detailsmentioning
confidence: 99%
“…Multiple studies have implicated TERRA as regulator of telomerase and telomere length (Sandell et al, 1994; Redon et al, 2010; Maicher et al, 2012; Pfeiffer and Lingner, 2012; Fei et al, 2015). TERRA has also been proposed to regulate recombination between telomeric ends (Balk et al, 2013; de Silanes et al, 2014; Yu et al, 2014) and serve as a scaffold for recruitment of chromatin factors such as HP1, histone methyltransferases, and shelterins to telomeric heterochromatin (Deng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Fei et al . have reported that the interaction between ESET and PRC2 maintains the pluripotency of ES cells. Thus, the down‐regulation of differentiation‐related genes by ESET may be crucial for maintaining the multipotency of mouse neural crest cells and for the formation of mouse NCSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Further adding to this lack of clarity on the role of JARID2 in modulation of PRC2 activity, in in vitro studies JARID2 appears to inhibit (Peng et al, 2009;Shen et al, 2009) as well as activate (Li et al, 2010) the methyltransferase activity of EZH2. A recent study has also shown that, in mouse ES cells, JARID2 can modulate PRC2 activity through its interaction with another histone methylase, setDB1 (Fei et al, 2015). A recent study has also shown that, in mouse ES cells, JARID2 can modulate PRC2 activity through its interaction with another histone methylase, setDB1 (Fei et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…It has been suggested that JARID2's N-terminal domain interacts with RNAs as well as nucleosomes (Son et al, 2013;Kaneko et al, 2014b) and its post-translational modifications determine its effect on PRC2 activity (Sanulli et al, 2015). A recent study has also shown that, in mouse ES cells, JARID2 can modulate PRC2 activity through its interaction with another histone methylase, setDB1 (Fei et al, 2015). JARID2-setDB1 interaction has also been identified in lineage-committed cells including lymphocytes (Macian et al, 2002;Pereira et al, 2014) and cardiomyocytes where JARID2 is shown to modulate other histone modifications such as H3K9me3.…”
Section: Introductionmentioning
confidence: 99%